2017
DOI: 10.1002/hed.24599
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a high‐observation protocol in major head and neck cancer surgery: A prospective study

Abstract: Rapid weaning of sedation and limiting mechanical ventilation may contribute to a shorter length of ICU admission and LOS, as well as decreased ICU readmissions. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1689-1695, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…31,32 An increasing body of work has also shown that post-operative free-flap monitoring is safe in appropriately selected head and neck cancer patients outside the intensive care unit. 20,22,23,30,33 Just under half of the patients in our cohort were mechanically ventilated, and the overall short patient length of stay in the intensive care unit suggests that some of the patients in our study admitted to the intensive care unit might have been suitable for post-operative care using an alternative pathway, freeing intensive care unit resources for other patients and decreasing the overall cost of each patient's admission.…”
Section: Discussionmentioning
confidence: 93%
“…31,32 An increasing body of work has also shown that post-operative free-flap monitoring is safe in appropriately selected head and neck cancer patients outside the intensive care unit. 20,22,23,30,33 Just under half of the patients in our cohort were mechanically ventilated, and the overall short patient length of stay in the intensive care unit suggests that some of the patients in our study admitted to the intensive care unit might have been suitable for post-operative care using an alternative pathway, freeing intensive care unit resources for other patients and decreasing the overall cost of each patient's admission.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study by Barber et al 29 looked at the utility of a CCP for expediting transfer from the ICU to the ward in HNC with microvascular reconstruction. The authors similarly initiated spontaneous breathing trials in the OR, and most but not all patients were spontaneously breathing upon arrival to the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 1). [10][11][12][13][14][15][16][17][18] The most common reasons for exclusion were wrong outcomes and inappropriate study design. Among the studies, there were 5 prospective cohort studies, 2 cross-sectional studies, and 2 retrospective cohort studies (Table 2).…”
Section: Search Termsmentioning
confidence: 99%